Robert K. Myers letter to Thomas H. Kent regarding bird sightings, December 11, 1979 - Myers, Robert K.et al (1979)
Field notes contributed by Robert K. Meyers in a letter to Thomas H. Kent, December 11, 1979. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1979. Epson - sheet feed/flatbed